Cryptococcosis by Cryptococcus gattii in immunocompetent goats in Spain and review of the literature - Torres-Rodríguez, Josep Maria; Mendoza, Miguel Hermoso de; Alvarado-Ramírez, Eidi; Segura-Roca, Gemma (Acta Scientiae Veterinariae, 2018)
Cryptococcus neoformans has been described for years as a species causing spontaneous mycosis in a great variety of animals. The new species C. gattii has been described as an agent of animal cryptococcosis mainly in Australia, but it has been found also in many parts of the world. The main group of animals suffering those natural infections are mammals, but also birds, reptiles and some invertebrates have suffered cryptococcosis. Usually the infections are sporadic and occasional, but some epidemic outbreaks have been reported affecting a high number of animals. In 1998 the isolation of C. gattii was reported by the first time in Europe in 5 epidemic outbreaks of cryptococcosis in goats grazing freely in west Spain grasslands. In all outbreaks, mycological studies were possible from samples obtained on necropsy of some animals dead during the epidemic. Animals belonged to various milking breeds and were grazing with variable status of health and husbandry. Goats affected by cryptococcosis showed similar respiratory symptoms, consisting in mucopurulent nasal discharge, cough, dyspnea and progressive cachexia, causing death in a period of 2 to 4 weeks. In three outbreaks many animals also showed ataxia, midriasis, blindness and progressive paralysis. Clinical prevalence varied from 2 to 12% in the different outbreaks. It is evident that in spite of the great amplitude of geographical distribution observed for C. gattii, this species has a limited presence, possibly restricted to determined habitats, as that of infection of goats flocks in Spain. Veterinarians must be concerned about Cryptococcosis in grazing animals. This finding introduced new elements connected to the epidemiology and ecology of Cryptococcus gattii.